Co-evolutionary dynamics of policy and system development: The case of marine renewable energy technologies - Fontes, M. (2018)
The transition to a sustainable energy system is a major societal challenge requiring profound transformations in existing socio-technical systems (Markard et al, 2012). These processes have been addressed by the sociotechnical transitions literature that called the attention to the role played by radically new technologies, being developed in niches, which have strong transformative potential (Kemp et al, 1998; Schot and Geels, 2007). These technologies and the socio-technical systems developing around them often need temporary protection against the selection pressures of the established regimes (Smith and Raven, 2016); and supportive policies are a fundamental mode of protection (Kivimaa and Kern, 2016). In the case of sustainable energy technologies, policy support is further justified by the need to accelerate the transition process (which is usually a long term process), given the urgency of fighting against climate change (IPCC, 2014).